2012
DOI: 10.1002/pd.3893
|View full text |Cite
|
Sign up to set email alerts
|

Fetal sex determination using cell‐free fetal DNA: service users' experiences of and preferences for service delivery

Abstract: Women were overwhelmingly positive about their experience of NIPD, which suggests that current delivery of this service in England is acceptable to these patients who are at high risk of sex-linked genetic disorders. They particularly valued expert counselling both before and after testing, emphasising that it should be offered through specialist services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 53 publications
(82 citation statements)
references
References 25 publications
4
78
0
Order By: Relevance
“…33 Similarly, a UK study found that women who have had NIPD for fetal sex determination described safety as the most important feature of the test. 34 For many women, the miscarriage risk associated with invasive testing is a psychological barrier to diagnostic testing for Down syndrome. 27,35 If the miscarriage risk is removed, women may feel more inclined to have a test.…”
Section: Discussionmentioning
confidence: 99%
“…33 Similarly, a UK study found that women who have had NIPD for fetal sex determination described safety as the most important feature of the test. 34 For many women, the miscarriage risk associated with invasive testing is a psychological barrier to diagnostic testing for Down syndrome. 27,35 If the miscarriage risk is removed, women may feel more inclined to have a test.…”
Section: Discussionmentioning
confidence: 99%
“…Terminated fetuses have been subject to trauma, and prolonged cell-culture often results in genetic changes (Sambuy et al 2005;Li et al 2007). Other fetal material used for diagnostic purposes includes cell-free DNA in the maternal blood, which has been applied clinically for fetal Rhesus D detection and gender determination since 2001 (Lewis et al 2012;Clausen 2014;Hyland et al 2014). More recently, cell-free fetal (cff ) DNA in maternal plasma has been used to screen for fetal aneuploidies (Song et al 2013;Bianchi et al 2014).…”
mentioning
confidence: 99%
“…However, other studies have shown that women value the opportunity to discuss their screening decisions in a personalised way with an appropriately trained health professional, 34 and there is no indication that this would be different in a diagnostic testing scenario. 35,36 In addition to this point, providing only written information assumes a level of literacy in the patient. We therefore recommend that individual discussion is undertaken to enable the woman to place the information into the context of her own life and that of her family.…”
Section: Discussionmentioning
confidence: 99%